2018
DOI: 10.1002/ece3.3921
|View full text |Cite
|
Sign up to set email alerts
|

Florivory indirectly decreases the plant reproductive output through changes in pollinator attraction

Abstract: Species often interact indirectly with each other via their traits. There is increasing appreciation of trait‐mediated indirect effects linking multiple interactions. Flowers interact with both pollinators and floral herbivores, and the flower‐pollinator interaction may be modified by indirect effects of floral herbivores (i.e., florivores) on flower traits such as flower size attracting pollinators. To explore whether flower size affects the flower‐pollinator interaction, we used Eurya japonica flowers. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
(63 reference statements)
1
20
0
Order By: Relevance
“…e) and a decline in microbial dispersal, but nectar concentration might be more likely to underlie the results that support hypothesis 2, as we observed a greater increase in nectar concentration in male flowers (Fig. e), whereas no obvious inherent difference in animal visitation was found between male and female flowers (Tsuji and Ohgushi ).…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…e) and a decline in microbial dispersal, but nectar concentration might be more likely to underlie the results that support hypothesis 2, as we observed a greater increase in nectar concentration in male flowers (Fig. e), whereas no obvious inherent difference in animal visitation was found between male and female flowers (Tsuji and Ohgushi ).…”
Section: Discussionsupporting
confidence: 48%
“…1a-d), including flies, midges, and bees. Previously, we reported that some of these insects were sometimes more frequently found around male plants than around female plants, but the difference was small and inconsistent between years (Tsuji and Ohgushi 2018). Floral longevity is similar between plant sexes (mean of 9 and 11 d for female and male flowers, respectively, in E. japonica; see Appendix S1: Table S1).…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…Flower diameter and length are approximately 2-5 mm and 3-5 mm, respectively. E. japonica is an insect-pollinated plant, its pollinators are mainly dipteran and thysanopteran insects (Kitamoto et al, 1992;Tsuji & Ohgushi, 2018), and its florivores are generally lepidopteran and dipteran larvae and hemipteran insects (Tsuji & Sota, 2013).…”
Section: Plant Materialsmentioning
confidence: 99%